Immunomodulation strategies against COVID-19 evidence: key nutrients and dietary approaches - Lindsey B. Cundra; Manasa Vallabhaneni; Michael Saadeh; Kevin V. Houston; Byung Soo Yoo; Steve D'Souza; David A. Johnson (Open Exploration Publishing Inc., 2023)
The novel coronavirus disease-2019 (COVID-19) has created a major public health crisis. Various dietary factors may enhance immunological activity against COVID-19 and serve as a method to combat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The dietary factors that are responsible for boosting immunity may provide a therapeutic advantage in patients with COVID-19. Investigators have demonstrated that vitamins B6, B12, C, D, E, and K, and trace elements like zinc, copper, selenium, and iron may serve as important tools for immunomodulation. Herein this is a review the peer-reviewed literature pertaining to dietary immunomodulation strategies against COVID-19. This review is intended to better define the evidence that dietary modifications and supplementation could positively influence the proinflammatory state in patients with COVID-19 and improve clinical outcomes. With appropriate insight, therapeutic interventions are discussed and directed to potentially modulate host immunity to mitigate the disease mechanisms of COVID-19.